Conservative Management of Segmental Infarction of the Greater Omentum: A Case Report and Review of Literature. (6th September 2010) - Soobrah, Ramawad; Badran, Mohammad; Smith, Simon G.
Abstract : Segmental omental infarction (SOI) is a rare cause of acute abdominal pain. Depending on the site of infarction, it mimics conditions like appendicitis, cholecystitis, and diverticulitis. Before the widespread use of Computed Tomography (CT), the diagnosis was usually made intraoperatively. SOI produces characteristic radiological appearances on CT scan; hence, correct diagnosis using this form of imaging may prevent unnecessary surgery. We present the case of a young woman who was treated conservatively after accurate radiological diagnosis.